Soft Touch using Soft Pneumatic Actuator–Skin as a Wearable Haptic Feedback Device. (25th January 2021) - Sonar, Harshal Arun; Huang, Jian-Lin; Paik, Jamie
Abstract : Understanding the external environment depends heavily on vision, audition, and touch. Like vision and audition, the human sense of touch is complex. Tactile perception is composed of multiple fundamental and physical experiences felt as changes in stiffness, texture, shape, size, temperature, and weight by the skin. While researchers and industries have made continuous efforts to abstract and recreate these haptic experiences, haptic devices are still limited in invoking intricate and rich sensations. Herein, the design, model, and experimental validation of a wearable skin‐like interface, able to recreate the roughness, shape, and size of a perceived object is presented; a platform for an interactive "physical" experience. The cogency of immersion through tactile feedback on moldable clay by the user response from the active haptic feedback, is examined. For the experimental test, a soft pneumatic actuator (SPA)‐skin interface (90 Hz bandwidth) with a complex actuation pattern is prototyped. The SPA‐skin's performance using three sets of simulated textures (<300 μm) and for reconstructing simulated contours (of a rectangle, circle, or trapezoid) in the virtual reality (VR) platform is investigated. The experimental results demonstrated for the first time how artificially created tactile feedback can indeed simulate physical interaction, with 83% average accuracy for contour reconstruction. Abstract : A platform for an interactive "physical" experience using a soft wearable skin‐like bi‐directional interface and a pliable test object is presented to recreate the roughness, shape, and size of a perceived object virtually. The cogency of immersion through tactile feedback is studied and validated experimentally, on a moldable clay using the user's response triggered by the active haptic feedback.